Electrical impedance tomography for neonatal ventilation assessment: a narrative review. (July 2019) - Masner, A; Blasina, F; Simini, F
Abstract: Neonatal care has improved dramatically over the last decades thanks to a better understanding of the transition to extrauterine life, especially due to the new respiration condition. A privileged technique to assess the filling of the lungs with air in a non-invasive way is Electrical Impedance Tomography (EIT), which is, therefore, also a tool to monitor ventilation. Out of 2427 papers on EIT from 1985 to 2018, 116 deal with EIT in neonatal care, with both the set and subset increasing at similar rates of 5 and 0.4 additional papers per year (0.03 and 0.05 papers per year) respectively. EIT can be used to determine Body position and Pneumothorax, to guide Endotracheal Tube Positioning and to monitor Ventilation Homogeneity. Moreover, real time EIT gives abundant evidence to develop new techniques such as Sustained Inflation, Protective Intended Ventilation, Minimal Invasive Surfactant Therapy, Less Invasive Surfactant Administration, Intubation-Surfactant-Extubation and Oro Pharyngeal Surfactant during their application to both animal models and patients. The low cost, non-invasive and easy graphic interpretation of EIT leads to the belief that it will have widespread use in Neonatal Medicine.